Aeolian harmonics: Murray Cox and Geoffrey Rowell. Issue 2 (3rd July 2018) - Williams, Rowan
ABSTRACT: Geoffrey Rowell enjoyed a long friendship with the psychiatrist Murray Cox, and this essay looks briefly at some of the areas in which their concerns converged. Murray Cox used the phrase 'the Aeolian mode' to describe forms of listening and interpreting in therapy which allowed buried connections to come into focus, and he explicitly linked this to some of the ways in which theology worked. Geoffrey Rowell embodied in particular ways the phenomenon of the 'Catholic Revival', in the nineteenth-century Church of England, with its sense of the force of mysteries, as in Pusey, and the need expressed, as in Newman and Keble, to approach them with 'reserve'. Attempts are made in the essay to trace some of the echoes and convergences.